2017
DOI: 10.2196/mental.8369
|View full text |Cite
|
Sign up to set email alerts
|

School Counselors’ Perspectives of a Web-Based Stepped Care Mental Health Service for Schools: Cross-Sectional Online Survey

Abstract: BackgroundMental health problems are common among youth in high school, and school counselors play a key role in the provision of school-based mental health care. However, school counselors occupy a multispecialist position that makes it difficult for them to provide care to all of those who are in need in a timely manner. A Web-based mental health service that offers screening, psychological therapy, and monitoring may help counselors manage time and provide additional oversight to students. However, for such… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 44 publications
(47 reference statements)
1
25
0
Order By: Relevance
“…During the development of the service, school counsellors, parents, and general practitioners (GPs) outlined various concerns related to the accuracy, effectiveness, and suitability of the service for delivery in the school setting [18-20]. Some parents questioned the effectiveness of a Web-based service for determining the level of care their child required [20] and whether the service would increase stigma among students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the development of the service, school counsellors, parents, and general practitioners (GPs) outlined various concerns related to the accuracy, effectiveness, and suitability of the service for delivery in the school setting [18-20]. Some parents questioned the effectiveness of a Web-based service for determining the level of care their child required [20] and whether the service would increase stigma among students.…”
Section: Discussionmentioning
confidence: 99%
“…Codesigned with students, school counsellors [18], general practitioners [19], and parents [20], the Black Dog Institute has developed a Web-based mental health service called Smooth Sailing. On the basis of the principles of stepped care, Smooth Sailing uses a website to screen, assess, allocate, and deliver psychological interventions to improve help-seeking for mental health problems and reduce depressive and anxiety symptoms among secondary school youth.…”
Section: Introductionmentioning
confidence: 99%
“…That is, to place school psychologists into the essential mix of services that is available to young Australians who are experiencing comorbid or multi-domain and/or multiservice issues. School psychologists are multi-specialists (O'Dea, King, Subotic-Kerry, O'Moore, & Christensen, 2017) and work at the coalface of youth mental health, so it is concerning that they are often precluded from research that attempts to encapsulate the range of mental health support services available to children and youth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, participants reported that GPs may be worried about data security and privacy. Although this is a common concern of internet-delivered care [ 24 , 25 , 32 ], participants felt that this could be alleviated by clear delineation of roles and responsibilities within the service alongside robust informed consent procedures with the young person. Additional barriers to acceptability of the proposed service included noncompliance by adolescents and GPs, as well as differences in mental health training and youth experience of GPs.…”
Section: Discussionmentioning
confidence: 99%
“…Acceptability research in health services aims to understand the extent to which people delivering or receiving an intervention consider it to be appropriate and suited to their needs, based on either anticipated or experimentation responses [ 31 ]. A study of the acceptability of the Smooth Sailing service among school counselors [ 32 ] found that personal beliefs, knowledge of e-mental health, internet accessibility, privacy, and confidentiality issues influenced their likelihood of use. Previous research on the adoption of eHealth among GPs has mainly been conducted in relation to adult health services [ 27 ].…”
Section: Introductionmentioning
confidence: 99%